2000
DOI: 10.18806/tesl.v18i1.899
|View full text |Cite
|
Sign up to set email alerts
|

Form-Focused Instruction in Communicative Language Teaching: Implications for Grammar Textbooks

Abstract: This article examines a number of adult ESL grammar textbooks via an authordesigned checklist to analyze how well they incorporate the findings from research in communicative language teaching (CLT) and in form1ocused instruction (FFI). It concludes that although afew textbooks incorporate some of the research findings in CLT and FFI, they are not necessarily those chosen by the teaching institutions. The Need for New GrammarIt has long been accepted by practitioners and academics alike that communicative lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The grammar aspect of language textbooks needs to be paid adequate attention to; authors must attempt to create texts that 'resemble natural speech' and allow easy flow from one sentence to another (Akyel, 2000). Wei (2021) has said that since Chinese is a formless language in which both word order and vocabulary are equally important in conveying the meaning, and although word order reflects a particular syntactic form and logic, its essence lies in the meaning that should be the core concentration in instruction.…”
Section: Resultsmentioning
confidence: 99%
“…The grammar aspect of language textbooks needs to be paid adequate attention to; authors must attempt to create texts that 'resemble natural speech' and allow easy flow from one sentence to another (Akyel, 2000). Wei (2021) has said that since Chinese is a formless language in which both word order and vocabulary are equally important in conveying the meaning, and although word order reflects a particular syntactic form and logic, its essence lies in the meaning that should be the core concentration in instruction.…”
Section: Resultsmentioning
confidence: 99%
“…The provision of adequate linguistic resources through literature is associated with linguistic accuracy. The acquisition of grammatical accuracy provides clear advantages to develop native-like abilities in written or oral language proficiency (Millard, 2000;Nusrat et al, 2019). The great majority of the participants reported that literature is a valuable input-rich source to improve accuracy.…”
Section: Accuracymentioning
confidence: 99%